Association between intracranial vessel calcifications, structural brain damage, and cognitive impairment after minor strokes: a prospective study - Seyman, Estelle Emanuelle; Sadeh-Gonik, Udi; Berman, Phillip; Blum, Itay; Shendler, Genady; Nathan, Bornstein; Rothschild, Ofer; Molad, Jeremy; Ben Assayag, Einor; Hallevi, Hen, the TABASCO prospective cohort study group (Frontiers in Neurology, 2023)
Background: Vascular calcifications are a hallmark of atherosclerosis, and in the coronary arteries are routinely used as a prognostic marker. Calcifications of intracranial vessels (ICC) are frequently observed on non-contrast CT (NCCT) and their effect on post-stroke cognitive impairment (PSCI) remains unclear. Our aim was to explore the association of ICC with prospective long-term cognitive function and advanced MRI-measures in a large prospective cohort cognitively intact of mild stroke survivors. Methods: Data from the Tel-Aviv brain acute stroke cohort (TABASCO) study [ClinicalTrials.gov#NCT01926691] were analyzed. This prospective cohort study(n=575) aimed to identify predictors of PSCI, in cognitively intact mild stroke survivors. A quantitative assessment of the intracranial calcium content -The ICC score (ICCS) was calculated semi-automatically on NCCT using a validated calcium quantification application. Participants underwent a 3T-MRI and prospective comprehensive cognitive clinical and laboratory assessments at enrollment, 6,12 and 24-months.Results: Data were available for 531 participants (67.4 years, 59.5% males). The incidence of PSCI at two-years doubled in the high ICCS group (26%vs.13.7%, p<0.001). The high ICCS group had significantly greater small-vessel-disease (SVD) tissue changes and reduced microstructural-integrity assessed by Diffusion-Tensor-Imaging(DTI) maps(p<0.05 for all). In multivariate analysis, higher ICCS was independently associated with brain atrophy manifested by lower normalized white and gray matter, hippocampal and thalamic volumes (β=-0.178, β=-0.2,β=-0.137,β=-0.157;p<0.05) and independently predicted PSCI (OR 1.83,.Our findings suggest that the ICCS, which is a simple and readily available imaging marker on NCCT, is associated with brain atrophy, microstructural damage, the